Pemerolehan Bahasa Pada Media Sosial Sebagai Kosa Kata Baru Bagi Generasi Z Di Sekolah - Wowoseko, Hilaria C. Aba; Taqdiraa, Taqdiraa; Kalukar, Ventje Jani (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
This research aims to determine the form and meaning of new vocabulary as one of the language variations in psycholinguistic studies used by Generation Z students as a result of acquiring language on social media. This research is descriptive qualitative research. The data collection technique was carried out using the listening method, namely listening to children's speech obtained from social media, using the Miles and Huberman data analysis technique. Activities in qualitative data analysis are carried out continuously until completion, so that the data is saturated, the analysis activities are reduction, data display and conclusion. The results of this research are that social media can influence children's (students') language acquisition in terms of psycholinguistics, that generation Z students acquire new vocabulary from social media to identify themselves, both for small groups and large groups, the use of this vocabulary also to get labeling that they keep up with the times as the word is used continuously.